Standardization and consumer acceptance of frozen squid (Sepiotheuthis lessoniana) balls - Santiago. Anna Theresa Banno (1994.)
This study standardized the production process for squid balls earlier developed by BFAR using Sepiothheuthis lessoniana. A preliminary study using 1 kg of raw squid was necessary for technical skills development and to standardize the process at laboratory scale. Volume measurements of ingredients were translated to percentage weights based on the major raw material. Five kilograms of raw squid was used in standardization to pilot scale. The finished product was subject to microbiological and physico-chemical analyses prior to sensory evaluation. In the second phase, a market survey of existing squid ball brands was conducted. Three popular brands were compared with the finished product. A consumer-type survey was also conducted on sixty respondents from four places. Results showed that the BFAR formulation, if sold commercially, has potentials in the market. Quality control points from raw material selection to in-process production and, finally, to finished product specifications were developed.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Squids